Engineering the frontier orbitals of a diazadiborinine for facile activation of H2, NH3, and an isonitrile - Su, Yuanting (2020)
An annulated 1,3,2,5‐diazadiborinine with 14 π electrons has been synthesized and fully characterized. Experimental and computational studies revealed that this compound features a rather small HOMO–LUMO gap, which leads to enhanced reactivity towards small molecules. Thus, the 1,3,2,5‐diazadiborinine readily cleaves the H−H bond of dihydrogen and an N−H bond of ammonia under mild conditions. Moreover, it reacts with 2,6‐dimethylphenylisonitrile in a [4+1] cycloaddition at room temperature.